Parental smartphone addiction and adolescent smartphone addiction by negative parenting attitude and adolescent aggression: A cross-sectional study - Doo, Eun-Young; Kim, Ji-Hye (Frontiers in Public Health, 2022)
This study aimed to examine the mediating role of negative parenting attitudes and adolescent aggression in the relationship between parents’ and adolescents’ smartphone addiction. This was a cross-sectional descriptive study that used data from the 2018 Korean Children and Youth Panel Survey. The study involved 2,360 adolescents (1,275 boys, 54.0%, mean age 14.52±0.33 years) and their parents (2,148 mothers, 91.0%), who used smartphones. Adolescents completed questionnaires assessing their negative parenting attitudes, aggression, and smartphone addiction while parents completed questionnaires assessing their sociodemographic characteristics and smartphone addiction. The results showed that parents’ smartphone addiction was directly and indirectly related to adolescents’ smartphone. Additionally, negative parenting attitudes and adolescent aggression played serial mediating roles in the relationship between parents’ smartphone addiction and adolescent smartphone addiction. Therefore, when developing interventions to prevention smartphone addiction among adolescents, it is necessary to consider parental smartphone addiction, positive parenting attitude, and adolescent aggression. Moreover, it highlighted the importance of developing healthy parenting environment that includes parents’ healthy smartphone use and positive parenting to prevent adolescents’ smartphone addiction.